Building resilience in port-cities: the role of open innovation and innovation ecosystems - Maria Rosilene Sabino; Maria do Rosário Cabrita; Marcela Souto Castro; Ana Mendes; Tiago Pinho (Discover Sustainability)
Abstract The port industry plays a vital role in the global economy by enhancing supply chain connectivity and supporting international trade. In recent years, disruptive events such as economic crises, environmental challenges, and technological advancements have profoundly reshaped the dynamics of seaports and port towns. Port cities represent complex ecosystems that integrate logistical, economic, and social activities, acting as critical nodes in the global trade network. The process of leveraging internal and external knowledge, alliances, and partnerships to accelerate innovation and improve problem-solving capabilities is known as open innovation. Conversely, innovation ecosystems describe linked networks of stakeholders—including businesses, governments, academia, and civil society—that cooperate to drive technical innovations and sustainable solutions. Both approaches are practical approaches to address complex challenges, encouraging collaboration and co-creation of solutions. However, their application in port cities and their influence on organisational and urban resilience require further investigation. Through a semi-systematic literature review, this study identifies key trends, challenges and opportunities associated with open innovation and innovation ecosystem, highlighting their potential to enhance resilience in port city contexts. Findings suggest that structured and inclusive collaboration significantly enhances urban and organisational adaptability, particularly in response to climate change and digital transformation pressures. A future research agenda is proposed to further investigate the long-term impacts of collaborative innovation on resilience in port cities.